2021
DOI: 10.1126/sciadv.abe0693
|View full text |Cite
|
Sign up to set email alerts
|

Common coding of expected value and value uncertainty memories in the prefrontal cortex and basal ganglia output

Abstract: Recent evidence implicates both basal ganglia and ventrolateral prefrontal cortex (vlPFC) in encoding value memories. However, comparative roles of cortical and basal nodes in value memory are not well understood. Here, single-unit recordings in vlPFC and substantia nigra reticulata (SNr), within macaque monkeys, revealed a larger value signal in SNr that was nevertheless correlated with and had a comparable onset to the vlPFC value signal. The value signal was maintained for many objects (>90) many weeks a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 57 publications
2
42
0
Order By: Relevance
“…We have previously shown that apart from the opposite polarity and differences in value signal magnitude, vlPFC and cdlSNr show remarkable similarities in encoding memory of object-reward associations (value memory) with a high-level of granularity 19 . Both vlPFC and cdlSNr have projections to superior colliculus (SC) and thus can work synergistically to promote finding and orienting toward valuable objects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that apart from the opposite polarity and differences in value signal magnitude, vlPFC and cdlSNr show remarkable similarities in encoding memory of object-reward associations (value memory) with a high-level of granularity 19 . Both vlPFC and cdlSNr have projections to superior colliculus (SC) and thus can work synergistically to promote finding and orienting toward valuable objects.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that value memories shape the visual responses of objects similarly and with a remarkable granularity in vlPFC and the basal ganglia output, SNr. 19 . However, it is not known whether the visual responses to objects in the corticobasal circuitry are also affected by other past experiential dimensions such as perceptual exposure (familiarity vs novelty) or aversive associations and if so whether the same neurons encode such disparate object memories across different domains.…”
Section: Introductionmentioning
confidence: 99%
“…We used the sessions with largest number of neurons for each of these two regions and merged all different grating conditions. vlPFC (areas 8Av, 46v, and 45) and SNr data are recorded in behaving macaques [42,44] and is available at [78]. The IpN data is from deep cerebellar nucleus of mice [40] and is available at [79].…”
Section: Methodsmentioning
confidence: 99%
“…Next, we checked response variability in another subcortical area namely substantia nigra reticula (SNr). This region was particularly informative for our analysis since here individual neurons showed large dynamic range of excitatory or inhibitory responses to visual objects based on their past value memory (excitation to low value objects and inhibition to high value objects, [42]). Fig 4a and 4b show responses of example neurons to high value and low value objects, respectively.…”
Section: Post-stimulus Enhancement Of Nc Canceling Reduction Of Nrv I...mentioning
confidence: 99%
“…More specifically, if we focus on the appetitive values of food items, we shall note that this type of subjective value depends on both the internal states of the subjects and their previous experience. Representations of value memory are reported in a couple of temporal and prefrontal cortices as well as in some basal regions in monkeys and humans ( Anderson et al, 2014 ; Kim et al, 2015 ; Ghazizadeh et al, 2020 ; Ghazizadeh and Hikosaka, 2021 ).…”
Section: Introductionmentioning
confidence: 99%